Towards understanding CRUMBS function in retinal dystrophies - Mélisande Richard; Ronald Roepman; Wendy M. Aartsen; Agnes G.S.H. van Rossum; Anneke I. den Hollander; Elisabeth Knust; Jan Wijnholds; Frans P.M. Cremers (2006)
Mutations in the Crumbs homologue 1 (CRB1) gene cause autosomal recessive retinitis pigmentosa (arRP) and autosomal Leber congenital amaurosis (arLCA). The crumbs (crb) gene was originally identified in Drosophila and encodes a large transmembrane protein required for maintenance of apico-basal cell polarity and adherens junction in embryonic epithelia. Human CRB1 and its two paralogues, CRB2 and CRB3, are highly conserved throughout the animal kingdom. Both in Drosophila and in vertebrates, the short intracellular domain of Crb/CRB organizes an evolutionary conserved protein scaffold. Several lines of evidence, obtained both in Drosophila and in mouse, show that loss-of-function of crb/CRB1 or some of its intracellular interactors lead to morphological defects and light-induced degeneration of photoreceptor cells, features comparable to those observed in patients lacking CRB1 function. In this review, we describe how understanding Crb complex function in fly and vertebrate retina enhances our knowledge of basic cell biological processes and might lead to new therapeutic approaches for patients affected with retinal dystrophies caused by mutations in the CRB1 gene.